Transventricular transforaminal endoscopic fenestration with cysto-ventriculoperitoneal shunt to manage a third ventricular arachnoid cyst: a case report - Yuliatri, Nia; Widjaya, Ingrid Ayke; Harlyjoy, Alphadenti; Wibawa, Gibran Aditiara; Satyanegara (Faculty of Medicine Universitas Indonesia, 2023)
Regular ventriculoperitoneal (VP) shunt is commonly used as the first option to manage a third ventricular arachnoid cyst due to the lack of facilities, unfamiliarity with endoscopic techniques, or misdiagnosis as purely obstructive hydrocephalus. A 9-year-old girl with obstructive hydrocephalus due to a third ventricular arachnoid cyst was treated with a VP shunt. 2 months later, the previous shunt device was removed due to an infection. Following a sterile cerebrospinal fluid analysis culture, we conducted a navigation-assisted transventricular transforaminal endoscopic fenestration and cysto-VP programmable shunt placement. A decrease in ventricular dilatation was seen on follow-up. This approach was justified due to the possibility of establishing communication with normal cisterns, the high rate of cyst elimination, and the potential for achieving shunt independence. Performing an endoscopic fenestration followed by cysto-VP shunt placement could be an optimal option for managing this condition.